2013
DOI: 10.1155/2013/914764
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strength and Biocompatibility of Ultrafine-Grained Commercial Purity Titanium

Abstract: The effect of grain refinement of commercial purity titanium by equal channel angular pressing (ECAP) on its mechanical performance and bone tissue regeneration is reported. In vivo studies conducted on New Zealand white rabbits did not show an enhancement of biocompatibility of ECAP-modified titanium found earlier by in vitro testing. However, the observed combination of outstanding mechanical properties achieved by ECAP without a loss of biocompatibility suggests that this is a very promising processing rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 21 publications
1
17
0
1
Order By: Relevance
“…This has been demonstrated by in vivo assays based on histology and micro-CT analyses. 66 Still, the overall performance of SPDprocessed titanium makes it very suitable for bone and tooth replacement. The ultimate proof for that has been provided in a most recent clinical study.…”
Section: Nanostructured Biomaterialsmentioning
confidence: 99%
“…This has been demonstrated by in vivo assays based on histology and micro-CT analyses. 66 Still, the overall performance of SPDprocessed titanium makes it very suitable for bone and tooth replacement. The ultimate proof for that has been provided in a most recent clinical study.…”
Section: Nanostructured Biomaterialsmentioning
confidence: 99%
“…In vivo studies, while not confirming such enhancement, demonstrated that a spectacular improvement of the mechanical performance of ECAP-modified commercial purity Ti was not accompanied by a loss of biocompatibility. [161] To further improve biocompatibility, it has been attempted (i) to replace Al and especially V with more biocompatible elements and (ii) to make Young's modulus close to that of bone in order to avoid the so-called 'stress shielding'. [162] In particular, Ti-Nb alloys have attracted a great deal of interest.…”
Section: Spd-processed Materials In Biomedical Applicationsmentioning
confidence: 99%
“…For example, in the ECAE process, the deformation zone moves along the workpiece when it passes through a die with angular channel. In this case, dead zones are formed at the edges of the workpiece [11][12][13][14][15][16][17][18][19][20][21]. Similar deformation conditions are realized during Twist Extrusion (TE) [5].…”
Section: Introductionmentioning
confidence: 99%